PERSEPSI KONSUMEN TERHADAP KUALITAS PELAYANAN SALON MAHASISWA PADA PRAKTIK MATA KULIAH MANAJEMEN USAHA SALON - Ika Prasetyani Pambudi (Jurnal Socia Akademika, 2023)
Consumers have high expectations for quality salon services because beautifying themselves and doing treatments at the salon has become a lifestyle for women. Therefore, this study aims to analyze consumer perceptions of the quality of student salon services in the practice of salon business management courses. This study used a qualitative descriptive approach with primary and secondary data types. Data collection techniques use questionnaires and interviews, which are then analyzed descriptively by percentage and qualitative analysis with interactive models. The result of the study is the perception of the quality of student salon services in the curriculum management practice course is included in the category of quite good. Service quality is considered the best in reliability, with a percentage of 67.9% in the suitable criteria. In comparison, the lowest percentage is the aspect of responsiveness (responsiveness), with a percentage of 64.3% in the criteria of good enough.